Pengaruh Kualitas Pelayanan Publik dan Manajemen Sumber Daya Manusia terhadap Kepuasan Masyarakat di Kantor Desa Sungkai Kecamatan Bajubang - Kasiyati Yunita Wulansari; Sri Rosmawati; Budi Darma (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
This study aims to analyze the influence of public service quality and human resource management on public satisfaction at the Sungkai Village Office, Bajubang District, both partially and simultaneously. The study employs a quantitative approach using a survey method. The population consists of community members receiving services at the Sungkai Village Office, while the sample comprises 60 respondents selected through purposive sampling. Data were collected via Likert-scale questionnaires and analyzed using multiple linear regression. The results indicate that public service quality and human resource management have a positive and significant effect on public satisfaction, both simultaneously and partially. This implies that improving public service quality—supported by effective human resource management—is a crucial factor in enhancing public satisfaction with the services provided at the Sungkai Village Office, Bajubang District.